Hungarian Monitoring, 3 June 1988 . [Magyar rádiófigyelő], 1988. június 3 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Evaluating the Soviet-American summit - Reagan in London - Sakharov's press conference in Moscow Domestic Affairs: - Interview with Central Committee secretary János Lukács - Grósz and Kádár invite Rajiv Gandhi - Hungary legally recognizes Mormon Church - Narcotics consumption Economy: - Greater budget deficit than planned - Reduction in iron smelting Külpolitika: - Szovjet-amerikai csúcs értékelése - Reagan Londonban - Szaharov sajtótájékoztató Moszkvában Belpolitika: - Interjú Lukács János KB titkárral - Grósz és Kádár meghívta Radzsiv Gandhit - Magyarország törvényesen elismeri a Mormon Egyházat - Kábítószer fogyasztás Gazdaság: - Nagyobb a költségvetési hiány a tervezettnél - A vaskohászat visszafejlesztése